THE SUBSTANTIATION OF THE PERIODIC PSYCHOPHYSIOLOGICAL RESEARCH SYSTEM WITH USE OF POLYGRAPH IN PERSONNEL WORKING PROCESS IN THE MINISTRY OF DEFENSE OF UKRAINE AND THE ARMED FORCES OF UKRAINE - Гришкин, С.; Кузьменко, М.; Халіманенко, С. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In accordance with the levels of corruption and other risks, potential areas of abuse in the areas of activity in the military sphere, with the purpose of exercising preventive influence on the personnel of the Ministry of Defense of Ukraine and the Armed Forces of Ukraine, as well as real prevention of offenses that could be committed, a survey of personnel using a polygraph in the Ministry of Defense and the Armed Forces of Ukraine. This system is a collection of individual elements, the combination of which creates a new property – the existence of constantly operating psychophysiological studies using a polygraph, conducted for certain categories of personnel for a predetermined time and agreed questions. This, in turn, will help to increase the effectiveness of using the polygraph in solving the problems of personnel security and the prevention of various kinds of offenses by the personnel of the Ministry of Defense of Ukraine and the Armed Forces of Ukraine. Key words: psychophysiological research of personnel using polygraph, preparation and adoption of personnel decisions, system of periodic inspections using polygraph, risks, potential areas of abuse, timing.